Long-Term Functional Consequences of Treatment of Fractures of the Distal Metaepiphysis of the Radius - Naumenko, L.Yu.; Mametiev, A.O.; Vinnyk, O.O. (TERRA ORTHOPAEDICA, 2023)
Summary. The frequency of damage to the distal metaepiphysis of the radius reaches from 16% to 33% of all fractures of the bones of the skeleton, and the increase in the incidence of osteoporosis definitely maintains the tendency to increase the frequency of damage to this localization. About 53.3% of the injured need repositioning; half of them (26.6%) have large unstable fractures of type B and C, which are subject to surgical treatment. Materials and Methods. The study was carried out based on the materials of the trauma centers and trauma departments of the “City Clinical Hospital No. 2” of the DCC (Dnipro) and the MNPE “City Clinical Hospital No. 6” of the DCC (Dnipro). To assess the long-term consequences, a retrospective analysis of archive records of 318 patients with damage to the distal metaepiphysis of the radius was performed, including 271 radiographs of females (85.2%) and 47 males (14.8%). Results. The conducted analysis gives grounds to state that remote manifestations depend on the nature and severity of fractures, the quality of reposition or surgical treatment. Fractures of type A and C have a pronounced tendency to develop manifestations of deforming arthrosis of the radiocarpal joint in the remote period after the injury, which may be due to the presence of incongruity of the articular surfaces against the background of residual “permissible” displacements of the fragments. Conclusions. Ensuring accurate repositioning of fractures and expanding the indications for surgical treatment in case of “permissible” displacement of bone fragments in fractures of the distal metaepiphysis of the radial bone will reduce the frequency and severity of arthrosis in the remote period after the injury.